BURIAL AND THERMAL HISTORY OF THE WEST BASHKIRIAN SEDIMENTARY BASINS - Galushkin Yu.I.; Yakovlev G.E. (My University, 2004)
The GALO system is applied to the numerical reconstruction of burial and thermal histories of the West Bashkirian lithosphere from the Riphean to the present. An analysis of the variation in tectonic subsidence of the basin during its development is utilized to estimate approximately the mantle heat flow variations. Our variant of basin evolution suggests that after cooling in the Early Riphean, the rather weak thermal reactivations have not led to considerable heating of the lithosphere in the study region. Surface heat flow decreased from relatively high values in the Early Riphean (60–70 mW/m2 in the eastern area and 40–50 mW/m2 in the western part) to present-day values of 32–40 mW/m2. In spite of the relatively low temperature regime of the basin as a whole, a syn-rifting deposition of more than 10 km of limestone, shale and sandstone in the Riphean resulted in rather high temperatures (180–190 °C) at the base of present-day sedimentary blanket in the eastern area. In agreement with the observed data, computed present-day heat flow through the sediment surface increases slightly from 32 to 34 mW/m2 near the west boundary of the region to 42 mW/m2 near the boundary of the Ural Foldbelt, whereas the heat flow through the basement surface decreases slightly from 28–32 to 24–26 mW/m2 in the same direction. The mantle heat flow is only 11.3–12.7 mW/m2, which is considerable lower than mean heat flow of the Russian Platform (16–18 mW/m2) and comparable with the low heat flow of Precambrian shields.
Keywords: West Bashkiria; Thermal and burial reconstruction; Basin modeling; Heat flow; Tectonic subsidence; Strength of the lithosphere; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей